2011
DOI: 10.1016/j.bandc.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between surface color and color knowledge: Behavioral and electrophysiological evidence

Abstract: In this study, we used event-related potentials (ERPs) to evaluate the contribution of surface color and color knowledge information in object identification. We constructed two color-object verification tasks - a surface and a knowledge verification task - using high color diagnostic objects; both typical and atypical color versions of the same object were presented. Continuous electroencephalogram was recorded from 26 subjects. A cluster randomization procedure was used to explore the differences between typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Lu and collaborators (Lu et al, 2010) found that black-and-white and atypically colored objects were associated with more negative amplitudes in this time window compared with typical color objects. In a previous color knowledge verification study, we also found a similar result: atypically colored objects generated a more negative N300 component than typically colored objects on the frontal sites, suggesting that the typical color presentation is better recognized and categorized than the atypical color presentation (Bramão et al, 2012). In the present study, we did not analyze the color effects in this time window because we did not find a clear N300 component in our ERPs waves.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Lu and collaborators (Lu et al, 2010) found that black-and-white and atypically colored objects were associated with more negative amplitudes in this time window compared with typical color objects. In a previous color knowledge verification study, we also found a similar result: atypically colored objects generated a more negative N300 component than typically colored objects on the frontal sites, suggesting that the typical color presentation is better recognized and categorized than the atypical color presentation (Bramão et al, 2012). In the present study, we did not analyze the color effects in this time window because we did not find a clear N300 component in our ERPs waves.…”
Section: Discussionsupporting
confidence: 78%
“…However, and beyond the facilitation that color information confers to the initial visual stages, our results showed a color effect in the later stages of object recognition for color diagnostic objects. At the later visual processing stages, color information might trigger the selection of the structural object description from long-term visual memory, which is matched to the perceptual input (Bramão et al, 2012). Additionally, the N400 color effect observed in this study suggests that color information might activate a more extensive object semantic network.…”
Section: Discussionmentioning
confidence: 61%
“…In a verification task involving HCD and LCD objects, in which participants had to indicate whether a written color name (e.g., “ red ”) matched the typical color of the target picture (e.g., “ strawberry ”), Bramão et al (2011a) found an effect of color knowledge in this time-window (N350). According to Bramão et al (2011a), their results suggest that this time-window is crucial for the integration of shape and color information, which can then be used to access structural representations of the object in long-term memory. Bramão et al (2011a) also point to previous literature showing that the N350 is “related to the selection of a stored structural description model to match against the perceptual input” (p. 35; citing Schendan and Kutas, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to Bramão et al (2011a), their results suggest that this time-window is crucial for the integration of shape and color information, which can then be used to access structural representations of the object in long-term memory. Bramão et al (2011a) also point to previous literature showing that the N350 is “related to the selection of a stored structural description model to match against the perceptual input” (p. 35; citing Schendan and Kutas, 2003). Bramão et al, (2012) suggest that the additional color information might be used to narrow down the number of possible structural features used to identify the object.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, if we directly compare priming across Experiments 1 and 2, there is a three-way interaction, F (2, 328) = 3.84, p = 0.022, η p 2 = 0.02, which provides strong evidence for the claim that names are better at activating color knowledge than shapes. Note, we are not suggesting that object-color knowledge cannot be used at a visual level of analysis, as there is convincing evidence for mappings between object shape and visual object-color information (e.g., Price and Humphreys, 1989; Bramão et al, 2012; Lloyd-Jones et al, 2012). Rather, we are proposing that object shape does not provide an effective retrieval cue in the lexical-semantic matching task.…”
Section: Resultsmentioning
confidence: 73%